Recovery of Sentence Production Processes Following Language Treatment in Aphasia: Evidence from Eyetracking - Mack, Jennifer E.; Nerantzini, Michaela; Thompson, Cynthia K. (Frontiers in Human Neuroscience, 2017)
Introduction: Sentence production impairments in aphasia often improve with treatment. However, little is known about how cognitive processes supporting sentence production, such as sentence planning, are impacted by treatment. Methods: The present study used eyetracking to examine changes in sentence production resulting from a 12-week language treatment program focused on passive sentences (Treatment of Underlying Forms (TUF); Thompson and Shapiro, 2005). In two pre-treatment and two post-treatment sessions, nine participants with mild-to-moderate agrammatic aphasia performed a structural priming task, which involved repeating primed sentences (actives or passives) and then, using the same verb, producing sentences describing pictured events. Two individuals with aphasia performed the eyetracking task on the same schedule without intervening language treatment. Ten unimpaired older adults also performed the task to identify normal performance patterns. Sentence production accuracy and speech onset latencies were examined, and eye movements to the pictured Agent and Theme characters were analyzed in the first 400 ms after picture onset, reflecting early sentence planning, and in the regions preceding the production of the sentence subject and post-verbal noun, reflecting lexical encoding. Results: Unimpaired controls performed with high accuracy. Their early eye movements (first 400 ms) indicated equal fixations to the Agent and Theme, consistent with structural sentence planning (i.e., initial construction of an abstract structural frame). Subsequent eye movements occurring prior to speech onset were consistent with encoding of the correct sentence subject (i.e., the Agent in actives, Theme in passives), with encoding of the post-verbal noun beginning at speech onset. In participants with aphasia, accuracy improved significantly with treatment, and post-treatment (but not pre-treatment) eye movements were qualitatively similar to those of unimpaired controls, indicating correct encoding of the Agent and Theme nouns for both active and passive sentences. Analysis of early eye movements also showed a treatment-induced increase in structural planning. No changes in sentence production accuracy or eye movements were found in the aphasic participants who did not receive treatment. Conclusion: These findings indicate that treatment improves sentence production and results in the emergence of normal-like cognitive processes associated with successful sentence production, including structural planning.